Creating Inclusive Culture of Elementary Schools: A Case Study in Karangmojo Sub-district, Gunungkidul Regency - Budiarti, Nugraheni Dwi; Sugito, Sugito (SCAD Independent, 2018)
Karangmojo Sub-District, Gunungkidul Regency Is One Of The Minus Areas In Various Aspects Of Life With The Highest Number Of Persons With Disabilities In The Special Region Of Yogyakarta, Indonesia. In This Area, The Forerunner Of Inclusive Education In Indonesia Was Born. The Purpose Of This Study Was To Reveal: A) Attitudes Of Teachers Toward Students With Special Needs As A Reflection Of The School's Inclusive Culture, B) Role Of Principals In Creating School Inclusive Culture, And C) School, Parent, And Community Partnership In Promoting Inclusive Culture. Data Collection Techniques Were Interviews, Observation, And Documentation. The Findings Showed That In General The Regular Teacher Showed A Positive Attitude To The Students With Special Needs In The Social Interaction, But Negative Attitudes Could Appear During Classroom Teaching Practices Involving The Presence Of Students With Special Needs. In General, The Support And Ability Of School Principals In Embracing All Parties In The Implementation Of Inclusive Education In Schools Helped To Support Creating Inclusive Culture In Schools. School, Parents, And Community Partnership Also Supported Creating An Inclusive Culture In Schools, But Were Often Constrained By The Social And Economic Conditions Of The Surrounding Community.